Pengaruh Penambahan Tepung Biji Nangka (Artocarpus Heterophyllus) Terhadap Karakteristik Bakso Ikan Tongkol (Euthynnus Affinis) - Idhapola Sitohang, Lenovia; Yusa, Ni Made; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
The purpose of this research was to know the effect of jackfruit seeds flour addition on tuna fish meatball characteristic and to determine the right amount of jackfruit seeds flour addition that produced tuna fish meatball with the best characteristics. This research used a completely randomized design with treatment consisting of 6 levels of concentration ratio of jackfruit seeds flour (0%, 5%. 10%, 15%, 20%, 25%). Each treatment repeated 3 times in order to obtain 18 experimental units. The data obtained were analysed by analysis of variance and if there was an effect, then it will be followed by the Duncan Multiple Range Test (DMRT). The result showed that the addition of jackfruit seeds flour had significant effect (p<0.05) on water content, carbohydrate content, crude fiber content, taste, texture score, and overall acceptance. The 10% addition of jackfruit seeds flour produced the best characteristics with 54.60% water content; 2.31% ash content; 21.68% protein content; 3.53% fat content; 17.89% carbohydrate content; 2.56% crude fiber content; the color, flavor, texture, taste and overall acceptance were slightly liked; and the texture was dense, compact, chewy.